Roles and Responsibilities Analysis of Substitution Notary Before Leaving Period - Andi Deny Zulkifli Nur; Achmad Sulchan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This research aims: 1) To find out the legal status of a substitution notary related to the notary who was replaced by a death before the leave ends. 2) Also to understand the administrative settlement mechanism for the Substitution notary Protocol related to the replaced Notary Public before the leave period ends. The research method used is Normative and Descriptive in nature which is supported by primary data and also references to books and related laws in the case of Substitute Notaries. Normative legal research is based on the logic of legal science from the normative side. It is descriptive in nature to present a complete picture of a problem and be described clearly. Based on the research, it is concluded that: In Article 35 paragraph 3 UUJN-P, namely that if the notary dies while on leave, then the duties of his office will be carried out by a substitution notary as a Notary's Temporary Officer no later than 30 (thirty) days from the date of the Notary's death. The administrative settlement mechanism for the Substitution notary Protocol, namely as a Notary Temporary Officer, has expired his term of office. The Regional Supervisory Council, then within 14 (fourteen) days from the end of the term of office of the Temporary Notary Officer, it is required to appoint a Notary as the recipient of the Notary protocol. Pursuant to Article 35 paragraph (4) UUJN-P that the Substitution notary Public as Temporary Officer of Notary Public has a period of submission of the Notary Public Protocol and the Substitution notary Public is no longer than 60 days from the death of the Notary Public.